Water Quality Indexes: Evolution and Trends at the Global Level - Castro, Mario; Almeida, Juniel; Ferrer, Julio; Diaz, Daissy (Ingeniería Solidaria, 2014)
The research project “Variables of Greatest Impact on Water Quality Indexes” (“Variables de mayor impacto sobre los indicadores de calidad del agua”) has been underway is at the Bogotá campus of the Universidad Cooperativa de Colombia since January of 2014. Its preliminary result was a review of precedents to identify relevant aspects in the design and construction of a knowledge-based software prototype that would help to improve water resource management. The study of water quality indexes during the period of analysis (1980-2014) is of fundamental importance to evaluate the influence of biotic and abiotic variables on a phenomenon/environment/area as relevant as water quality. The authors analyzed experimental reports supplied by specialized publications and national and international governmental organizations. Analysis of the information showed that one of the most important methodologies to determine water quality is the use of ica indexes, a mathematical tool that facilitates the transformation of large amounts of data into a single measurement scale.
Keywords: water quality; environmental indexes; water quality indexes (ICA); sustainable development; environmental sustainability